Preparation method of optical polyester resin and film

The core-shell structure catalyst was prepared by precipitation method and the use of strong magnets to separate it, which solved the problem that the catalyst residue affected the transparency of polyester, and achieved the preparation of optical grade polyester resin and film without catalyst residue, which improved the light transmittance and polycondensation of the film Catalytic activity of ester resin.

CN119409953APending Publication Date: 2025-02-11MIANYANG VOCATIONAL & TECH COLLEGE +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411459715.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Catalyst residue will affect the transparency of polyester slices or films, and the prior art is difficult to remove or separate the catalyst, resulting in problems such as decreased transparency, higher haze and gel spot formation in the synthesis of polyester resin.

Method used

The core-shell structure catalyst was prepared by precipitation method. Through the preparation of magnetic core-shell structure catalysts, including the preparation of Fe3O4@SiO2/Sb2O3 and Fe3O4@SiO2@ethylene glycol antimony, the catalyst was effectively separated by using a strong magnet.

Benefits of technology

The optical grade polyester resin and film preparation without catalyst residue is achieved. The film has high light transmittance and low haze, which meets the use requirements of high-end optical films, and improves the intrinsic viscosity and catalytic activity of the polyester resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409953A_ABST
    Figure CN119409953A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of optical polyester resin and a film. The preparation method comprises the following steps: S1, preparing a magnetic core-shell structure catalyst; according to the preparation method of the optical-grade polyester resin and the film, the core-shell structure catalyst is prepared through a precipitation method, the preparation method is simple, the polyester resin prepared through the method has no catalyst residues, the film processing process is easier to carry out, due to the fact that the heterogeneous nucleation effect of the catalyst does not exist, the film is not prone to crystallization, and the optical-grade polyester resin is obtained. The optical thin film is high in light transmittance and small in haze, meets the use requirements of high-end optical thin films, adopts a multi-layer coating mode to synthesize a multi-layer structure catalyst, can effectively separate the catalyst through a magnetic separation mode to prepare polyester resin without catalyst residues, and then prepares the optical thin film through a synchronous two-way stretching mode. The obtained polyester resin or film has the remarkable characteristic of no catalyst residue, and the film is high in light transmittance, low in haze and less in film impurities or crystal points.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer material synthesis and processing, and in particular to a method for preparing an optical grade polyester resin and a film. Background Art

[0002] Polyethylene terephthalate (abbreviated as polyester or PET) is a type of engineering plastic with excellent performance developed in the 1950s. It is a polymer material formed by esterification reaction of terephthalic acid and ethylene glycol. Polyester resin can usually be processed into film by biaxial stretching. The product has the advantages of high mechanical strength, good transparency, low price, good dimensional stability, good insulation performance, etc. It is widely used in liquid crystal displays, tapes, insulated motors, food packaging, photovoltaic power generation and other fields.

[0003] Antimony trioxide, antimony glycol, titanate, etc. are usually used as catalysts in the synthesis of PET resin. The catalyst cannot be separated after the synthesis of the material is completed and will continue to exist in the melt or the finished product. Due to the residual catalyst, the transparency of the PET film after biaxial stretching will decrease and the haze will increase. At the same time, the residual catalyst will continue to react with the molecular chain segments at high temperature, increase the molecular weight, form a gel point or affect the melt fluidity. CN112795997A discloses a method for preparing a multiphase titanium-based polyester catalyst. Titanium dioxide is attached to the pores of a porous carrier to make the molecular weight distribution of the polyester narrower. However, due to the introduction of carrier components, more inorganic substances are present, which is not conducive to improving the transparency of the polyester film. CN105860045A discloses a method for preparing a multiphase titanium-based polyester catalyst. The method uses basic aluminum acetate as a raw material, partially hydrolyzes to form a γ-AlOOH compound, and needs to be used in combination with a co-catalyst such as ethylene glycol antimony. The prepared polyester has a light transmittance of 91-92% and a haze of less than 1%, which meets the requirements for the use of optical materials. However, the aluminum compound will be hydrolyzed during the synthesis or use process to generate aluminum hydroxide, which causes the presence of the catalyst to affect the optical properties. According to reports in public patents and literature, catalyst residues will affect the transparency of polyester chips or films, but polyester resin catalysts cannot be removed or separated. The current common method is to increase the activity of the catalyst to reduce the amount of the catalyst so as to reduce the effect of the catalyst on transparency. Usually, there are catalyst residues in the synthesis of polyester resins, and the residual catalysts will affect transparency and react to form gel substances.

[0004] Therefore, it is necessary to provide a method for preparing an optical grade polyester resin and a film to solve the above technical problems. Summary of the invention

[0005] The present invention provides a method for preparing an optical-grade polyester resin and a film, which solves the problem that catalyst residues will affect the transparency of polyester chips or films, but the polyester resin catalyst cannot be removed or separated. The common method at present is to increase the activity of the catalyst to reduce the amount of the catalyst so as to reduce the influence of the catalyst on the transparency. Usually, there are catalyst residues in the synthesis of polyester resins, and the residual catalysts will affect the transparency and react to form gel substances.

[0006] In order to solve the above technical problems, the present invention provides a method for preparing an optical grade polyester resin and a film, comprising the following steps: S1: Preparation of a magnetic core-shell structure catalyst:

[0007] S11: Weigh 0.09 mol of ferrous sulfate and place it in a beaker of 5 g / L polyethylene glycol (PEG200, PEG400, PEG600, PEG800 or PEG1000) aqueous solution. Place it in a 30°C constant temperature water bath and add dilute ammonia water dropwise while stirring until the pH value of the solution is 11 and the solution turns dark green. Then add 2.7 mL of hydrogen peroxide and the solution turns black. Continue stirring for 20 min. Transfer the mixed solution into a hydrothermal kettle and keep the temperature at 160°C for 5 h. Finally, cool, wash and dry to obtain Fe3O4 powder with a spherical structure.

[0008] S12: Add 100 mL of polyethylene glycol 200, 30 ml of deionized water and spherical Fe3O4 powder into a three-necked flask, adjust the pH value with dilute ammonia water, add 200 mL of ethanol, stir for 1 h, then add SbCl3 ethanol solution (concentration of 7 g / mL) and ethyl orthosilicate dropwise, stir for 1 h, filter and wash 3 times, and dry at 80 °C to obtain the core-shell catalyst Fe3O4@SiO2 / Sb2O3;

[0009] S13: Add the catalyst Fe3O4@SiO2 / Sb2O3 prepared in the second step into a single-necked flask, then add excess anhydrous ethanol, react at 70°C with stirring for 5 hours, condense and reflux the ethanol to remove a small amount of water, and finally cool, filter, wash, and dry the core-shell structure catalyst Fe3O4@SiO2@ethylene glycol antimony at 60°C;

[0010] S2: Preparation of optical polyester resin: 2 mol of terephthalic acid and 2.2 mol of ethylene glycol are added to a three-necked glass bottle, and the temperature is raised while stirring fully and the initial pressure in the glass bottle is controlled to 0.2 MPa. When the temperature in the glass bottle rises to 230-250°C, the water distilled from esterification is collected, and the esterification rate is calculated by the water output. When the esterification rate reaches 97%, the pressure is slowly released, and the prepared core-shell structure catalyst is added, and then 0.001 mol of triphenyl phosphate is added as a stabilizer. Stir for 30 minutes, and then slowly vacuum is started. When the pressure in the glass bottle is less than or equal to 60 Pa, the temperature is raised to 260-275°C for polycondensation reaction. The polycondensation time is 4-7 hours, and then N2 is filled to prevent oxidation. Under the heating state, a strong magnet is installed under the glass bottle. After 1 hour, the upper layer of resin is taken out, and then crushed and granulated to obtain a catalyst-free optical polyester resin;

[0011] S3: Preparation of biaxially stretched optical polyester film: The optical polyester resin was dried at 165°C for 2-3h, added to a single screw extruder with a screw diameter of 20mm and an aspect ratio of 35:1, melted at 275-285°C, and cooled on a cold drum at 15°C. Synchronous biaxial stretching was then performed on a static biaxial stretching test machine with a preheating time of 120s and a stretching temperature of 100-130°C.

[0012] Preferably, the concentration of the SbCl3 ethanol solution in step S12 is 7 g / mL.

[0013] Preferably, the diameter of the spherical Fe3O4 powder is 10-50 nm.

[0014] Preferably, in the Fe3O4@SiO2 / Sb2O3 catalyst prepared in the second step, SiO2 and Sb2O3 are dispersed on the surface of Fe3O4, intertwined to form a mixed shell structure, and the content of SiO2 and Sb2O3 is adjusted by the addition amount of SbCl3 and tetraethyl orthosilicate. The SiO2:Sb2O3 (mass ratio) in the Fe3O4@SiO2 / Sb2O3 catalyst is 0-100% (i.e., the Sb2O3 content in the overall catalyst is 0-1.94%).

[0015] Preferably, the polyethylene glycol is a mixture of one or more of PEG200, PEG400, PEG600, PEG800 or PEG1000.

[0016] Preferably, the catalyst Fe3O4@SiO2@ethylene glycol antimony uses Fe3O4@SiO2 / Sb2O3 as raw material, so that Sb2O3 is completely converted into ethylene glycol antimony, and the epitaxially generated ethylene glycol antimony forms a third layer interface to prepare a Fe3O4@SiO2@ethylene glycol antimony catalyst.

[0017] Preferably, the intrinsic viscosity of the optical polyester resin is 0.6-0.85 dl / g, and more preferably the intrinsic viscosity is 0.67-0.75 dl / g.

[0018] Preferably, the b value of the optical polyester resin is 2-5, the biaxial stretching ratio is 2.8-4 times, and the thickness of the biaxially stretched optical film is 0.03-0.1 mm.

[0019] Preferably, a water bath heating box is required for the constant temperature water bath, and a water bath tank is provided on one side of the top of the water bath heating box, and a mounting arm is rotatably installed on the other side of the top of the water bath heating box, and a movable groove is provided on one side of the surface of the mounting arm, and a threaded rod is rotatably installed inside the movable groove, and an adjusting block is fixedly installed on one end of the threaded rod, and a movable plate is threadedly engaged with the outer surface of the threaded rod, and a support box is fixedly installed on one side of the movable plate, a placement groove is provided on the surface of the support box, and a connecting hole is provided on the outer surface of the support box, and threaded holes are provided on three sides of the surface of the support box, and a threaded rod is threadedly engaged with the inner thread of the threaded hole, and a limiting plate is rotatably installed on one end of the threaded rod.

[0020] Preferably, a display screen is fixedly mounted on one side of the front face of the water bath heating box, and a temperature regulator is rotatably mounted on the other side of the front face of the water bath heating box.

[0021] Compared with the related art, the preparation method of an optical grade polyester resin and film provided by the present invention has the following beneficial effects:

[0022] The invention provides a method for preparing an optical-grade polyester resin and a film. The core-shell structure catalyst is prepared by a precipitation method. The preparation method is simple and has strong operability. The content of Sb2O3 or ethylene glycol antimony in the catalyst center of the surface layer can be precisely controlled, and the activity intensity of the catalyst can be selectively controlled. SiO2 and Sb2O3 form a mixed shell structure, and the active center Sb2O3 is dispersed in the SiO2 network structure. Relying on the porous structure of SiO2, the reactant is more likely to contact the catalyst active center, so that the prepared core-shell structure catalyst has stronger activity. When the Sb2O3 content is low, the catalyst active center is less, and the catalytic synthesis effect on polyester is weak. As the Sb2O3 content increases, the catalytic effect is significantly enhanced. However, when the Sb2O3 content is too high, the SiO2 porous structure cannot be formed, and Sb2O3 forms a dense cluster structure, which is not conducive to the active center participating in the esterification reaction, but reduces the catalytic effect. The core-shell structure catalysts Fe3O4@SiO2 / Sb2O3 and Fe3O4@SiO2@ethylene glycol antimony, due to the internal The core uses spherical Fe3O4, which has obvious magnetic characteristics, and the catalyst can be effectively separated by a strong magnet. The prepared polyester resin and film pass the iron element test, indicating that there is no obvious catalyst residue; the core-shell structure catalyst has a network surface structure, and the catalytic active centers are distributed in the network channels, which can improve the catalytic activity, shorten the reaction time of synthesizing the polyester resin, and also improve the characteristic viscosity; the polyester resin prepared by the method of the present invention has no catalyst residue, which makes the film processing process easier to carry out. Since there is no heterogeneous nucleation effect of the catalyst, the film is not easy to crystallize. The optical film has high light transmittance and low haze, which meets the use requirements of high-end optical films. A multi-layer structure catalyst is synthesized by a multi-layer coating method, and then the catalyst can be effectively separated by a magnetic separation method to prepare a polyester resin without catalyst residue, and then an optical film is prepared by a synchronous biaxial stretching method. The obtained polyester resin or film has the significant characteristic of no catalyst residue, and can be prepared into a film by biaxial stretching. The film has high light transmittance, low haze, and fewer impurities or crystal points. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A transmission electron microscope photograph of a core-shell structure catalyst in a method for preparing an optical-grade polyester resin and film provided by the present invention;

[0024] Figure 2 It is a schematic diagram showing the effect of the Sb2O3 content in the Fe3O4@SiO2 / Sb2O3 catalyst on the viscosity of PET;

[0025] Figure 3 A schematic structural diagram of a sixth embodiment of a method for preparing an optical-grade polyester resin and a film provided by the present invention;

[0026] Figure 4 for Figure 3Schematic diagram of the side view of the water bath heating box shown.

[0027] Numbers in the figure: 1. Water bath heating box, 2. Water bath, 3. Mounting arm, 4. Support box, 5. Threaded rod, 6. Limit plate, 7. Display screen, 8. Temperature regulator, 9. Moving groove, 10. Threaded rod, 11. Adjustment block, 12. Moving plate, 13. Placement groove, 14. Connecting hole, 15. Threaded hole. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with the accompanying drawings and implementation modes.

[0029] First embodiment

[0030] Please refer to Figure 1 and Figure 2 ,in, Figure 1 A transmission electron microscope photograph of a core-shell structure catalyst in a method for preparing an optical-grade polyester resin and film provided by the present invention; Figure 2 The figure is a schematic diagram showing the effect of the Sb2O3 content in the Fe3O4@SiO2 / Sb2O3 catalyst on the viscosity of PET. A method for preparing an optical grade polyester resin and a film comprises the following steps: S1: Preparation of a magnetic core-shell structure catalyst:

[0031] S11: Weigh 0.09 mol of ferrous sulfate and place it in a beaker of 5 g / L polyethylene glycol (PEG200, PEG400, PEG600, PEG800 or PEG1000) aqueous solution. Place it in a 30°C constant temperature water bath and add dilute ammonia water dropwise while stirring until the pH value of the solution is 11 and the solution turns dark green. Then add 2.7 mL of hydrogen peroxide and the solution turns black. Continue stirring for 20 min. Transfer the mixed solution into a hydrothermal kettle and keep the temperature at 160°C for 5 h. Finally, cool, wash and dry to obtain Fe3O4 powder with a spherical structure.

[0032] S12: Add 100 mL of polyethylene glycol 200, 30 ml of deionized water and spherical Fe3O4 powder into a three-necked flask, adjust the pH value with dilute ammonia water, add 200 mL of ethanol, stir for 1 h, then add SbCl3 ethanol solution (concentration of 7 g / mL) and ethyl orthosilicate dropwise, stir for 1 h, filter and wash 3 times, and dry at 80 °C to obtain the core-shell catalyst Fe3O4@SiO2 / Sb2O3;

[0033] S13: Add the catalyst Fe3O4@SiO2 / Sb2O3 prepared in the second step into a single-necked flask, then add excess anhydrous ethanol, react at 70°C with stirring for 5 hours, condense and reflux the ethanol to remove a small amount of water, and finally cool, filter, wash, and dry the core-shell structure catalyst Fe3O4@SiO2@ethylene glycol antimony at 60°C;

[0034] S2: Preparation of optical polyester resin: 2 mol of terephthalic acid and 2.2 mol of ethylene glycol are added to a three-necked glass bottle, and the temperature is raised while stirring fully and the initial pressure in the glass bottle is controlled to 0.2 MPa. When the temperature in the glass bottle rises to 230-250°C, the water distilled from esterification is collected, and the esterification rate is calculated by the water output. When the esterification rate reaches 97%, the pressure is slowly released, and the prepared core-shell structure catalyst is added, and then 0.001 mol of triphenyl phosphate is added as a stabilizer. Stir for 30 minutes, and then slowly vacuum is started. When the pressure in the glass bottle is less than or equal to 60 Pa, the temperature is raised to 260-275°C for polycondensation reaction. The polycondensation time is 4-7 hours, and then N2 is filled to prevent oxidation. Under the heating state, a strong magnet is installed under the glass bottle. After 1 hour, the upper layer of resin is taken out, and then crushed and granulated to obtain a catalyst-free optical polyester resin;

[0035] S3: Preparation of biaxially stretched optical polyester film: The optical polyester resin was dried at 165°C for 2-3h, added to a single screw extruder with a screw diameter of 20mm and an aspect ratio of 35:1, melted at 275-285°C, and cooled on a cold drum at 15°C. Synchronous biaxial stretching was then performed on a static biaxial stretching test machine with a preheating time of 120s and a stretching temperature of 100-130°C.

[0036] The concentration of the SbCl3 ethanol solution in step S12 is 7 g / mL.

[0037] The diameter of the spherical Fe3O4 powder is 10-50nm.

[0038] In the Fe3O4@SiO2 / Sb2O3 catalyst prepared in the second step, SiO2 and Sb2O3 are dispersed on the surface of Fe3O4, interweaving with each other to form a mixed shell structure, and the content of SiO2 and Sb2O3 is adjusted by the addition amount of SbCl3 and tetraethyl orthosilicate. The SiO2:Sb2O3 (mass ratio) in the Fe3O4@SiO2 / Sb2O3 catalyst is 0-100% (that is, the Sb2O3 content in the overall catalyst is 0-1.94%).

[0039] The polyethylene glycol is one or more mixtures of PEG200, PEG400, PEG600, PEG800 or PEG1000.

[0040] The catalyst Fe3O4@SiO2@ethylene glycol antimony uses Fe3O4@SiO2 / Sb2O3 as raw materials, so that Sb2O3 is completely transformed into ethylene glycol antimony, and the epitaxially generated ethylene glycol antimony forms a third layer interface to prepare a Fe3O4@SiO2@ethylene glycol antimony catalyst.

[0041] The intrinsic viscosity of the optical polyester resin is 0.6-0.85 dl / g, and more preferably the intrinsic viscosity is 0.67-0.75 dl / g.

[0042] The b value of the optical polyester resin is 2-5, the biaxial stretching ratio is 2.8-4 times, and the thickness of the biaxially stretched optical film is 0.03-0.1 mm.

[0043] according to Figure 2 The effect of the Sb2O3 content in the Fe3O4@SiO2 / Sb2O3 catalyst on the viscosity of PET can be observed. As can be seen from the figure, when the surface layer does not contain Sb2O3, there is no catalytic active center on the surface, and there is no obvious catalytic effect on the synthesis of polyester resin. The intrinsic viscosity of the synthesized resin is only 0.41dL / g. As the Sb2O3 content in the core-shell structure catalyst increases, the catalytic effect continues to improve, and the intrinsic viscosity of the polyester resin increases. When the Sb2O3 content reaches 1.3%, the intrinsic viscosity of PET reaches 0.82dL / g. However, when the Sb2O3 content continues to increase, the intrinsic viscosity of PET decreases instead, and drops to the lowest at a content of 1.94% (at this time, there is no SiO2 on the surface of the catalyst, forming a Fe3O4@Sb2O3 catalyst). This is mainly because there is no SiO2 to form a pore structure, and Sb2O3 will form a dense surface structure, which greatly reduces the specific surface area of ​​the surface, and reduces the catalytic centers that the reactants can contact, resulting in a decrease in catalytic activity.

[0044] The first embodiment is a blank control sample. There is no Sb2O3 in the catalyst and there is almost no catalytic effect, so that the intrinsic viscosity of the synthesized PET resin is only 0.41 dL / g and the b value is 2, which makes it impossible to perform biaxial film stretching processing.

[0045] Example 2

[0046] Weigh 0.09 mol of ferrous sulfate and place it in a beaker of 5 g / L PEG200 aqueous solution. Place it in a 30°C constant temperature water bath and add dilute ammonia water while stirring continuously until the pH value of the solution is 11 and the solution turns dark green. Then add 2.7 mL of hydrogen peroxide and the solution turns black. Continue stirring for 20 minutes, transfer the mixed solution to a hydrothermal kettle, keep the temperature at 160°C for 5 hours, and finally cool, wash, and dry to obtain spherical Fe3O4 powder.

[0047] Then add 100mL polyethylene glycol 200, 30ml deionized water and spherical Fe3O4 powder into a three-necked flask, adjust the pH value with dilute ammonia water, add 200mL ethanol, stir for 1h, then add SbCl3 ethanol solution (concentration of 7g / mL) and tetraethyl orthosilicate dropwise at the same time, stir for 1h, filter and wash 3 times, and dry at 80°C to obtain a core-shell structure catalyst Fe3O4@SiO2 / Sb2O3, with a Sb2O3 content of 0.19% in the catalyst.

[0048] 2 mol of terephthalic acid and 2.2 mol of ethylene glycol are added to a three-necked glass bottle, and the temperature is raised with sufficient stirring and the initial pressure in the glass bottle is controlled to 0.2 MPa. When the temperature in the glass bottle rises to 230-250°C, the esterification distilled water is collected, and the esterification rate is calculated by the water output. When the esterification rate reaches 97%, the pressure is slowly released, and the prepared core-shell structure catalyst is added, and then 0.001 mol of triphenyl phosphate is added as a stabilizer. Stir for 30 minutes, and then slowly vacuum is started. When the pressure in the glass bottle is ≤60Pa, the temperature is raised to 275°C for polycondensation reaction. The polycondensation time is 4-7h, and N2 is then filled to prevent oxidation. Under the heating state, a strong magnet is installed under the glass bottle. After 1 hour, the upper resin is taken out, and then crushed and granulated to obtain a catalyst-free optical polyester resin.

[0049] The optical polyester resin was dried at 165°C for 2-3h, added to a single screw extruder with a screw diameter of 20mm and an aspect ratio of 35:1, melted at 275°C, and cooled on a cold drum at 15°C. Synchronous biaxial stretching was then performed on a static biaxial stretching tester with a preheating time of 120s, a stretching temperature of 100°C, and a stretching multiple of 2.8*2.8.

[0050] Example 3

[0051] Weigh 0.09 mol of ferrous sulfate and place it in a beaker of 5 g / L PEG800 aqueous solution. Place it in a 30°C constant temperature water bath and add dilute ammonia water while stirring continuously until the pH value of the solution is 11 and the solution turns dark green. Then add 2.7 mL of hydrogen peroxide and the solution turns black. Continue stirring for 20 minutes, transfer the mixed solution to a hydrothermal kettle, keep the temperature at 160°C for 5 hours, and finally cool, wash, and dry to obtain spherical Fe3O4 powder.

[0052] Then add 100mL polyethylene glycol 200, 30ml deionized water and spherical Fe3O4 powder into a three-necked flask, adjust the pH value with dilute ammonia water, add 200mL ethanol, stir for 1h, then add SbCl3 ethanol solution (concentration of 7g / mL) and tetraethyl orthosilicate dropwise at the same time, stir for 1h, filter and wash 3 times, and dry at 80°C to obtain a core-shell structure catalyst Fe3O4@SiO2 / Sb2O3, with a Sb2O3 content of 1.3% in the catalyst.

[0053] 2 mol of terephthalic acid and 2.2 mol of ethylene glycol are added to a three-necked glass bottle, and the temperature is raised with sufficient stirring and the initial pressure in the glass bottle is controlled to 0.2 MPa. When the temperature in the glass bottle rises to 230-250°C, the esterification distilled water is collected, and the esterification rate is calculated by the water output. When the esterification rate reaches 97%, the pressure is slowly released, and the prepared core-shell structure catalyst is added, and then 0.001 mol of triphenyl phosphate is added as a stabilizer. Stir for 30 minutes, and then slowly vacuum is started. When the pressure in the glass bottle is ≤60Pa, the temperature is raised to 265°C for polycondensation reaction. The polycondensation time is 4-7h, and N2 is then filled to prevent oxidation. Under the heating state, a strong magnet is installed under the glass bottle. After 1 hour, the upper resin is taken out, and then crushed and granulated to obtain a catalyst-free optical polyester resin.

[0054] The optical polyester resin was dried at 165°C for 2-3h, added to a single screw extruder with a screw diameter of 20mm and an aspect ratio of 35:1, melted at 285°C, and cooled on a cold drum at 15°C. Synchronous biaxial stretching was then performed on a static biaxial stretching test machine with a preheating time of 120s, a stretching temperature of 130°C, and a stretching multiple of 4*4.

[0055] Example 4

[0056] The catalyst Fe3O4@SiO2 / Sb2O3 prepared in Example 3 was added to a single-necked flask, and then an excess of anhydrous ethanol was added, and the mixture was stirred at 70°C for 5 hours, and the ethanol was refluxed by condensation to remove a small amount of water. Finally, the core-shell structure catalyst Fe3O4@SiO2@ethylene glycol antimony was cooled, filtered, washed, and dried at 60°C.

[0057] 2 mol of terephthalic acid and 2.2 mol of ethylene glycol are added to a three-necked glass bottle, and the temperature is raised with sufficient stirring and the initial pressure in the glass bottle is controlled to 0.2 MPa. When the temperature in the glass bottle rises to 230-250°C, the esterification distilled water is collected, and the esterification rate is calculated by the water output. When the esterification rate reaches 97%, the pressure is slowly released, and the prepared core-shell structure catalyst is added, and then 0.001 mol of triphenyl phosphate is added as a stabilizer. The mixture is stirred for 30 minutes, and then the vacuum is slowly drawn until the pressure in the glass bottle is ≤60Pa. The temperature is raised to 270°C for polycondensation reaction. The polycondensation time is 4-7 hours, and then N2 is filled to prevent oxidation. Under the heating state, a strong magnet is installed under the glass bottle. After 1 hour, the upper resin is taken out, and then crushed and granulated to obtain a catalyst-free optical polyester resin.

[0058] The optical polyester resin was dried at 165°C for 2-3h, added to a single screw extruder with a screw diameter of 20mm and an aspect ratio of 35:1, melted at 280°C, and cooled on a cold drum at 15°C. Synchronous biaxial stretching was then performed on a static biaxial stretching test machine with a preheating time of 120s, a stretching temperature of 120°C, and a stretching multiple of 3*3.

[0059] Example 5

[0060] Weigh 0.09 mol of ferrous sulfate and place it in a beaker of a mixed aqueous solution of PEG200 and PEG800 at a concentration of 5 g / L. Place it in a 30°C constant temperature water bath and add dilute ammonia water while stirring continuously until the pH value of the solution is 11, and the solution turns dark green. Then add 2.7 mL of hydrogen peroxide and the solution turns black. Continue stirring for 20 minutes, transfer the mixed solution to a hydrothermal kettle, keep the temperature at 160°C for 5 hours, and finally cool, wash, and dry to obtain spherical Fe3O4 powder.

[0061] Then add 100mL polyethylene glycol 200, 30ml deionized water and spherical Fe3O4 powder into a three-necked flask, adjust the pH value with dilute ammonia water, add 200mL ethanol, stir for 1h, then add SbCl3 ethanol solution (concentration is 7g / mL), stir for 1h, filter and wash 3 times, and dry at 80°C to obtain a core-shell structure catalyst Fe3O4@Sb2O3. The catalyst does not contain SiO2 and the Sb2O3 content is 1.94%.

[0062] 2 mol of terephthalic acid and 2.2 mol of ethylene glycol are added to a three-necked glass bottle, and the temperature is raised with sufficient stirring and the initial pressure in the glass bottle is controlled to 0.2 MPa. When the temperature in the glass bottle rises to 230-250°C, the esterification distilled water is collected, and the esterification rate is calculated by the water output. When the esterification rate reaches 97%, the pressure is slowly released, and the prepared core-shell structure catalyst is added, and then 0.001 mol of triphenyl phosphate is added as a stabilizer. Stir for 30 minutes, and then slowly vacuum is started. When the pressure in the glass bottle is ≤60Pa, the temperature is raised to 275°C for polycondensation reaction. The polycondensation time is 4-7h, and N2 is then filled to prevent oxidation. Under the heating state, a strong magnet is installed under the glass bottle. After 1 hour, the upper resin is taken out, and then crushed and granulated to obtain a catalyst-free optical polyester resin.

[0063] The optical polyester resin was dried at 165°C for 2h, added to a single screw extruder with a screw diameter of 20mm and an aspect ratio of 35:1, melted at 275°C, and cooled on a cold drum at 15°C. Synchronous biaxial stretching was then performed on a static biaxial stretching tester with a preheating time of 120s, a stretching temperature of 105°C, and a stretching multiple of 3.3*3.3.

[0064] The performance indicators of the optical polyester resin and film prepared in Examples 2 to 5 are shown in Table 1

[0065] Table 1: Performance index table of optical polyester resin and film tape prepared in Examples 2 to 5

[0066]

[0067] It can be concluded from the data shown in Table 1 that the preparation process of the core-shell structure catalyst of the present invention is relatively simple, the operability is strong, the active center in the catalyst can be accurately controlled, and the catalyst has Fe3O4 as the core, which has the advantage of being magnetically separable. When the core-shell structure catalyst is used to synthesize polyester resin, the surface Sb2O3 or ethylene glycol antimony content will have a significant effect on the viscosity of the PET resin. The synthesis process is simple and easy. The synthesized catalyst can be effectively separated by a strong magnet, so that there is no catalyst residue in the PET resin. The iron content is extremely low, which is better for the appearance of the resin. The prepared catalyst-free optical polyester resin can be processed into a film on existing melt extrusion and biaxial stretching equipment. The film thickness is controllable, the insulation performance is excellent, the light transmittance is high, the haze is low, and the use requirements of high-end optical films are met. It has very high processing formability and application prospects, and provides a new idea for the synthesis of optical polyester resins and film processing.

[0068] The working principle of the preparation method of an optical grade polyester resin and film provided by the present invention is as follows:

[0069] At work, first the preparation of magnetic core-shell structure catalyst:

[0070] (1) Weigh 0.09 mol of ferrous sulfate and place it in a beaker of 5 g / L polyethylene glycol (PEG200, PEG400, PEG600, PEG800 or PEG1000) aqueous solution. Place it in a 30°C constant temperature water bath and add dilute ammonia water dropwise while stirring until the pH value of the solution is 11 and the solution turns dark green. Then add 2.7 mL of hydrogen peroxide and the solution turns black. Continue stirring for 20 min, transfer the mixture into a hydrothermal kettle, keep the temperature at 160°C for 5 h, and finally cool, wash and dry to obtain spherical Fe3O4 powder.

[0071] (2) Add 100 mL of polyethylene glycol 200, 30 mL of deionized water and spherical Fe3O4 powder into a three-necked flask, adjust the pH value with dilute ammonia water, add 200 mL of ethanol, stir for 1 hour, then add SbCl3 ethanol solution (concentration of 7 g / mL) and tetraethyl orthosilicate dropwise, stir for 1 hour, filter and wash three times, and dry at 80°C to obtain the core-shell structure catalyst Fe3O4@SiO2 / Sb2O3.

[0072] (3) The catalyst Fe3O4@SiO2 / Sb2O3 prepared in the second step was added to a single-necked flask, and then an excess of anhydrous ethanol was added. The mixture was stirred at 70°C for 5 h, and the ethanol was refluxed by condensation to remove a small amount of water. Finally, the core-shell structure catalyst Fe3O4@SiO2@ethylene glycol antimony was cooled, filtered, washed, and dried at 60°C.

[0073] 2. Preparation of optical polyester resin:

[0074] 2 mol of terephthalic acid and 2.2 mol of ethylene glycol are added to a three-necked glass bottle, and the temperature is raised with sufficient stirring and the initial pressure in the glass bottle is controlled to 0.2 MPa. When the temperature in the glass bottle rises to 230-250°C, the esterification distilled water is collected, and the esterification rate is calculated by the water output. When the esterification rate reaches 97%, the pressure is slowly released, and the prepared core-shell structure catalyst is added, and then 0.001 mol of triphenyl phosphate is added as a stabilizer. Stir for 30 minutes, and then slowly vacuum is started. When the pressure in the glass bottle is less than or equal to 60 Pa, the temperature is raised to 260-275°C for polycondensation reaction. The polycondensation time is 4-7 hours, and N2 is then filled to prevent oxidation. Under the heating state, a strong magnet is installed under the glass bottle. After 1 hour, the upper layer of resin is taken out, and then crushed and granulated to obtain a catalyst-free optical polyester resin.

[0075] 3. Preparation of biaxially stretched optical polyester film:

[0076] The optical polyester resin was dried at 165°C for 2-3h, added to a single screw extruder with a screw diameter of 20mm and an aspect ratio of 35:1, melted at 275-285°C, and cooled on a cold drum at 15°C. Synchronous biaxial stretching was then performed on a static biaxial stretching test machine with a preheating time of 120s and a stretching temperature of 100-130°C.

[0077] Compared with the related art, the preparation method of an optical grade polyester resin and film provided by the present invention has the following beneficial effects:

[0078] The present invention provides a method for preparing an optical-grade polyester resin and a film. A core-shell structure catalyst is prepared by a precipitation method. The preparation method is simple and has strong operability. The content of Sb2O3 or ethylene glycol antimony in the catalyst center of the surface layer can be precisely controlled, and the activity intensity of the catalyst can be selectively controlled. SiO2 and Sb2O3 are formed into a mixed shell structure, and the active center Sb2O3 is dispersed in the SiO2 network structure. Relying on the porous structure of SiO2, reactants are more easily in contact with the catalyst active center, so that the prepared core-shell structure catalyst is more active. When the Sb2O3 content is low, the catalyst has fewer active centers and the catalytic synthesis of polyester is weak; as the Sb2O3 content increases, the catalytic effect is significantly enhanced; but when the Sb2O3 content is too high, the SiO2 porous structure cannot be formed, and Sb2O3 forms a dense cluster structure, which is not conducive to the active center participating in the esterification reaction, but reduces the catalytic effect; the core-shell structure catalysts Fe3O4@SiO2 / Sb2O3 and Fe3O4@SiO2@ethylene glycol antimony have obvious magnetic characteristics because the inner core uses spherical Fe3O4, and the catalyst can be effectively separated by a strong magnet. The prepared polyester resin and film have passed the iron element test, indicating that there is no obvious catalyst residue; the core-shell structure catalyst has a network surface structure, and the catalytic active center is separated. Distributed in the mesh channels, the catalytic activity can be improved, the reaction time of synthesizing polyester resin can be shortened, and the characteristic viscosity can also be increased; the polyester resin prepared by the method of the present invention has no catalyst residue, so that the film processing process is easier to carry out, and since there is no heterogeneous nucleation effect of the catalyst, the film is not easy to crystallize, the optical film has high light transmittance and low haze, and meets the use requirements of high-end optical films. A multi-layer structure catalyst is synthesized by a multi-layer coating method, and then the catalyst can be effectively separated by a magnetic separation method to prepare a polyester resin without catalyst residue, and then an optical film is prepared by a synchronous biaxial stretching method. The obtained polyester resin or film has the remarkable characteristic of no catalyst residue, and can be prepared into a film by biaxial stretching. The film has high light transmittance, low haze, and fewer impurities or crystal points.

[0079] Sixth embodiment

[0080] Please refer to Figure 3 and Figure 4 Based on the method for preparing an optical-grade polyester resin and a film provided in the first embodiment of the present application, the sixth embodiment of the present application proposes another method for preparing an optical-grade polyester resin and a film. The sixth embodiment is only a preferred method of the first embodiment, and the implementation of the sixth embodiment will not affect the independent implementation of the first embodiment.

[0081] Specifically, the sixth embodiment of the present application provides a method for preparing an optical-grade polyester resin and film. The difference is that, in the method for preparing an optical-grade polyester resin and film, a water bath heating box 1 is required for the constant temperature water bath, and a water bath tank 2 is provided on one side of the top of the water bath heating box 1, and a mounting arm 3 is rotatably installed on the other side of the top of the water bath heating box 1, and a movable groove 9 is provided on one side of the surface of the mounting arm 3, and a threaded rod 10 is rotatably installed inside the movable groove 9, and an adjusting block 11 is fixedly installed at one end of the threaded rod 10, and a movable plate 12 is threadedly engaged with the outer surface of the threaded rod 10, and a support box 4 is fixedly installed on one side of the movable plate 12, and a placement groove 13 is provided on the surface of the support box 4, and a connecting hole 14 is provided on the outer surface of the support box 4, and threaded holes 15 are provided on three sides of the surface of the support box 4, and the threaded rod 10 is threadedly engaged with the inner thread of the threaded hole 15, and a limiting plate 6 is rotatably installed at one end of the threaded rod 10.

[0082] A display screen 7 is fixedly mounted on one side of the front face of the water bath heating box 1 , and a temperature regulator 8 is rotatably mounted on the other side of the front face of the water bath heating box 1 .

[0083] The working principle of the preparation method of an optical grade polyester resin and film provided by the present invention is as follows:

[0084] During operation, first place the beaker inside the placement groove 13, rotate the adjustment block to drive the threaded rod 5 to rotate, the threaded rod 5 threadedly engages the moving plate 12 to drive the tray 4 to move up and down, and then rotate the mounting arm 3 to make the beaker inside the placement groove 13 detach from the water bath and easy to take out.

[0085] Compared with the related art, the preparation method of an optical grade polyester resin and film provided by the present invention has the following beneficial effects:

[0086] The present invention provides a method for preparing an optical-grade polyester resin and a film. The threaded rod 5 is driven to rotate by rotating an adjusting block. The threaded rod 5 is threadably engaged with a moving plate 12 to drive a tray 4 to move up and down. Then, the mounting arm 3 is rotated so that a beaker in a placement groove 13 is separated from a water bath and can be conveniently taken out. The device has a simple structure and strong practicality. It avoids the situation in which the beaker has to wait for too long to cool down after being water bathed, which makes it inconvenient to take out, and improves the convenience of operation.

[0087] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing an optical grade polyester resin and a film, characterized in that: The following steps are involved: S1: Preparation of magnetic core-shell catalysts: S11: Weigh 0.09 mol of ferrous sulfate and place it in a beaker of polyethylene glycol aqueous solution with a concentration of 5 g / L. Place it in a constant temperature water bath at 30°C and add dilute ammonia water dropwise while stirring continuously until the pH value of the solution is 11 and the solution turns dark green. Then add 2.7 mL of hydrogen peroxide and the solution turns black. Continue stirring for 20 min. Transfer the mixed solution into a hydrothermal kettle and keep the temperature at 160°C for 5 h. Finally, cool, wash and dry to obtain Fe3O4 powder with a spherical structure. S12: Add 100 mL of polyethylene glycol 200, 30 ml of deionized water and spherical Fe3O4 powder into a three-necked flask, adjust the pH value with dilute ammonia water, add 200 mL of ethanol, stir for 1 hour, then add SbCl3 ethanol solution and ethyl orthosilicate dropwise at the same time, stir for 1 hour, filter and wash 3 times, and dry at 80°C to obtain the core-shell structure catalyst Fe3O4@SiO2 / Sb2O3; S13: Add the catalyst Fe3O4@SiO2 / Sb2O3 prepared in the second step into a single-necked flask, then add excess anhydrous ethanol, react at 70°C with stirring for 5 hours, condense and reflux the ethanol to remove a small amount of water, and finally cool, filter, wash, and dry the core-shell structure catalyst Fe3O4@SiO2@ethylene glycol antimony at 60°C; S2: Preparation of optical polyester resin: 2 mol of terephthalic acid and 2.2 mol of ethylene glycol are added to a three-necked glass bottle, and the temperature is raised while stirring fully and the initial pressure in the glass bottle is controlled to 0.2 MPa. When the temperature in the glass bottle rises to 230-250°C, the water distilled from esterification is collected, and the esterification rate is calculated by the water output. When the esterification rate reaches 97%, the pressure is slowly released, and the prepared core-shell structure catalyst is added, and then 0.001 mol of triphenyl phosphate is added as a stabilizer. Stir for 30 minutes, and then slowly vacuum is started. When the pressure in the glass bottle is less than or equal to 60 Pa, the temperature is raised to 260-275°C for polycondensation reaction. The polycondensation time is 4-7 hours, and then N2 is filled to prevent oxidation. Under the heating state, a strong magnet is installed under the glass bottle. After 1 hour, the upper layer of resin is taken out, and then crushed and granulated to obtain a catalyst-free optical polyester resin; S3: Preparation of biaxially stretched optical polyester film: The optical polyester resin was dried at 165°C for 2-3h, added into a single screw extruder with a screw diameter of 20mm and an aspect ratio of 35:

1. After melting at 275-285°C, the cast sheet was cooled on a cold drum at 15°C, and then synchronously biaxially stretched on a static biaxial stretching testing machine with a preheating time of 120s and a stretching temperature of 100-130°C.

2. The method for preparing an optical grade polyester resin and film according to claim 1, characterized in that: The concentration of the SbCl3 ethanol solution in step S12 is 7 g / mL.

3. The method for preparing an optical grade polyester resin and film according to claim 1, characterized in that: The diameter of the spherical Fe3O4 powder is 10-50nm.

4. The method for preparing an optical grade polyester resin and film according to claim 1, characterized in that: In the Fe3O4@SiO2 / Sb2O3 catalyst prepared in the second step, SiO2 and Sb2O3 are dispersed on the surface of Fe3O4, interweaving with each other to form a mixed shell structure. The content of SiO2 and Sb2O3 is adjusted by the addition amount of SbCl3 and tetraethyl orthosilicate. The SiO2:Sb2O3 in the Fe3O4@SiO2 / Sb2O3 catalyst is 0-100%.

5. The method for preparing an optical grade polyester resin and film according to claim 1, characterized in that: The polyethylene glycol is one or more mixtures of PEG200, PEG400, PEG600, PEG800 or PEG1000.

6. The method for preparing an optical grade polyester resin and film according to claim 1, characterized in that: The catalyst Fe3O4@SiO2@ethylene glycol antimony uses Fe3O4@SiO2 / Sb2O3 as raw materials, so that Sb2O3 is completely transformed into ethylene glycol antimony, and the epitaxially generated ethylene glycol antimony forms a third layer interface to prepare a Fe3O4@SiO2@ethylene glycol antimony catalyst.

7. The method for preparing an optical grade polyester resin and film according to claim 1, characterized in that: The intrinsic viscosity of the optical polyester resin is 0.6-0.85 dl / g, and more preferably the intrinsic viscosity is 0.67-0.75 dl / g.

8. The method for preparing an optical grade polyester resin and film according to claim 1, characterized in that: The b value of the optical polyester resin is 2-5, the biaxial stretching ratio is 2.8-4 times, and the thickness of the biaxially stretched optical film is 0.03-0.1 mm.

9. The method for preparing an optical grade polyester resin and film according to claim 1, characterized in that: A water bath heating box is required for the constant temperature water bath, a water bath tank is provided on one side of the top of the water bath heating box, a mounting arm is rotatably installed on the other side of the top of the water bath heating box, a movable groove is provided on one side of the surface of the mounting arm, a threaded rod is rotatably installed inside the movable groove, an adjusting block is fixedly installed on one end of the threaded rod, a movable plate is threadedly engaged on the outer surface of the threaded rod, a support box is fixedly installed on one side of the movable plate, a placement groove is provided on the surface of the support box, a connecting hole is provided on the outer surface of the support box, threaded holes are provided on three sides of the surface of the support box, a threaded rod is threadedly engaged inside the threaded hole, and a limiting plate is rotatably installed on one end of the threaded rod.

10. The method for preparing an optical grade polyester resin and film according to claim 9, characterized in that: A display screen is fixedly mounted on one side of the front of the water bath heating box, and a temperature regulator is rotatably mounted on the other side of the front of the water bath heating box.

Citation Information

Patent Citations

  • Special optical polyester synthesis catalyst and preparation method and application thereof

    CN105860045A

  • Preparation method of micro-branched titanium polyester melt direct spinning POY filaments

    CN112795997A